Occupations Associated With Severe Acute Respiratory Syndrome Coronavirus 2 Infection and Vaccination, US Blood Donors, May 2021–December 2021. (14th November 2022) - Shah, Melisa M; Spencer, Bryan R; Feldstein, Leora R; Haynes, James M; Benoit, Tina J; Saydah, Sharon H; Groenewold, Matthew R; Stramer, Susan L; Jones, Jefferson M
Abstract: Background: There are limited data on the risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the United States by occupation. We identified occupations at higher risk for prior SARS-CoV-2 infection as defined by the presence of infection-induced antibodies among US blood donors. Methods: Using a nested case-control study design, blood donors during May–December 2021 with anti-nucleocapsid (anti-N) testing were sent an electronic survey on employment status, vaccination, and occupation. The association between previous SARS-CoV-2 infection and occupation-specific in-person work was estimated using multivariable logistic regression adjusting for sex, age, month of donation, race and ethnicity, education, vaccination, and telework. Results: Among 85 986 included survey respondents, 9504 (11.1%) were anti-N reactive. Healthcare support (20.3%), protective service (19.9%), and food preparation and serving related occupations (19.7%) had the highest proportion of prior infection. After adjustment, prior SARS-CoV-2 infection was associated with healthcare practitioners (adjusted odds ratio [aOR], 2.10; 95% confidence interval [CI], 1.74–2.54) and healthcare support (aOR, 1.82; 95% CI, 1.39–2.40) occupations compared with computer and mathematical occupations as the referent group. Lack of coronavirus disease 2019 vaccination (aOR, 16.13; 95% CI, 15.01–17.34) and never teleworking (aOR, 1.17; 95% CI, 1.05–1.30) were also independently associated with prior SARS-CoV-2 infection. Construction and extraction occupations had the highest proportion of unvaccinated workers (30.5%). Conclusions: Workers in healthcare, protective services, and food preparation had the highest prevalence of prior SARS-CoV-2 infection. Occupational risks for SARS-CoV-2 infection remained after adjusting for vaccination, telework, and demographic factors. These findings underscore the need for mitigation measures and personal protection in healthcare settings and other workplaces. Abstract : Among more than 80 000 US blood donors who underwent SARS-CoV-2 serologic testing and provided detailed employment information, prior infection was most common among workers in healthcare, protective services, and food preparation. Occupational risks remained after adjusting for demographics, vaccination, and telework.